Isomerization and Decomposition of a Criegee Intermediate in the Ozonolysis of Alkenes: Dynamics Using a Multireference Potential1. (13th November 2013) - Kalinowski, Jaroslaw; Räsänen, Markku; Heinonen, Petri; Kilpeläinen, Ilkka; Gerber, R. Benny
Abstract The isomerization and decomposition dynamics of the simplest Criegee intermediate CH2OO have been studied by classical trajectory simulations using the multireference ab initio MR‐PT2 potential on the fly. A new, accelerated algorithm for dynamics with MR‐PT2 was used. For an initial temperature of 300 K, starting from the transition state from CH2OO→CH2O2 , the system reaches the dioxirane structure in around 50 fs, then isomerizes to formic acid (in ca. 2800 fs), and decomposes into CO+H2O at around 2900 fs. The contributions of different configurations to the multiconfigurational total electronic wave function vary dramatically along the trajectory, with diradical contributions being important for transition states corresponding to H‐atom transfers, while being only moderately significant for CH2OO. The implications for reactions of Criegee intermediates are discussed.